Balancing Tradition and Modernity: Islamic Education in the Evolution of Wetu Telu in Northern Lombok - Nasri, Ulyan; Muliadi, Erlan; Rasyidi, Abdul Haris (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2024)
This research explores Wetu Telu Islam, focusing on Islamic Religious Education Values: Continuity and Efforts of Islamic Da'wah-Education of Wetu Telu Islam in the Context of the Five-Time Islam, resilience, and adaptation within the religious landscape of the Sasak community in North Lombok, West Nusa Tenggara. Wetu Telu Islam, a unique form of Islam, is rarely studied within the context of religious diversity in Indonesia. This study uses a qualitative approach, collecting data through participatory observation, in-depth interviews, and document analysis. The findings reveal how Wetu Telu Islam integrates into the daily lives of the Sasak community in North Lombok, highlighting the role of cultural values, traditions, and local wisdom in sustaining this tradition. Additionally, the research uncovers the role of Islamic Religious Education Values as a crucial spiritual foundation in shaping the community’s identity and morals, illustrating how values such as moral integrity, religious knowledge, and adaptable teachings contribute to the enduring relevance of Wetu Telu Islam amid the development of Five-Time Islam. This study emphasizes how Wetu Telu Islam not only survives but also adapts in response to the influence of more formal Islamic traditions. The integration of Islamic Religious Education Values offers a deeper understanding of how the Sasak community maintains their ancestral values while accommodating the dynamics of modern religious beliefs. The research aims to enrich the understanding of Wetu Telu Islam as an evolving tradition and provide insights for developing inclusive policies that support religious diversity in Indonesia, particularly in West Nusa Tenggara.